2019
DOI: 10.1021/acs.joc.9b02130
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Aptitudes in Rearrangements of Destabilized Vinyl Cations

Abstract: The Lewis acid-promoted generation of destabilized vinyl cations from β-hydroxy diazo ketones leads to an energetically favorable 1,2-shift across the alkene followed by an irreversible C–H insertion to give cyclopentenone products. This reaction sequence overcomes typical challenges of counter-ion trapping and rearrangement reversibility of vinyl cations and has been used to study the migratory aptitudes of nonequivalent substituents in an uncommon C­(sp2) to C­(sp) vinyl cation rearrangement. The migratory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The unreacted 1q was recovered in 35% yield with 99% ee ( s factor = 16) . These results matched well with the migration order for the pinacol rearrangement. ,, …”
supporting
confidence: 75%
“…The unreacted 1q was recovered in 35% yield with 99% ee ( s factor = 16) . These results matched well with the migration order for the pinacol rearrangement. ,, …”
supporting
confidence: 75%
“…A range of primary, secondary, cyclic or acyclic alkyl-substituted alkynes could be employed in the hydrofluorination to furnish respective products again with moderate to good yields and excellent regio-and stereoselectivities (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Remarkably, substrates with potentially sensitive functional groups including a primary chloro, a carboxymethyl, a cyano, a pyridyl, and a phthalimido group also delivered the monofluoroalkene products, highlighting the mildness and good functional group tolerance of this protocol (40)(41)(42)(43)(44)(45)(46). This scalability of the procedure was demonstrated by the gram-scale preparation of 44, which proceeded with unchanged regio-and stereoselectivities and only a slightly reduced yield (1.65 g, 64%).…”
Section: Resultsmentioning
confidence: 99%
“…2 ) as shown in Scheme . As part of our studies into the mechanism of the vinyl cation C−H insertion reaction, we modeled the reaction pathway computationally, which showed that the Lewis acid mediated dehydroxylation step was reversible, and that the rate limiting step of this sequence is formation of the vinyl cation by loss of N 2 from the vinyl diazonium intermediate. This led us to consider that it might be possible to intercept vinyl diazonium intermediate 2 with a nucleophile other than OH prior to N 2 dissociation to give a more complex product that still retains the diazo fragment.…”
Section: Methodsmentioning
confidence: 99%